Factors Affecting the Intention to Study a Master's Degree Abroad of Vietnamese Students and Recommendations - Anh, Nguyen Thi Mai; Tam, Le Nguyen Thanh; Nguyen, Nguyen An; An, Mai Thai Binh (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Recently, there has been an annual increase in the number of masters in Vietnam. In contrast, universities in Vietnam do not recruit enough master's students to meet the set goals. This is due, in part, to the fact that students frequently pursue master's degrees abroad. This study aimed to determine the factors influencing students' intentions to pursue a master's degree abroad in engineering and economics. The proposed research model is based on Ajzen's Theory of Planned Behavior (TPB) (1991), developed from the previous Theory of Reasoned Action in 1975, and incorporates related studies. This model includes the factors that influence the intention to study for a master's degree—attitude, subjective norm, perceived behavioral control, communication, reasonable cost, and career opportunities—and the factors that influence the attitude to study for a master's degree. 434 valid samples for analysis, conducted several methods, including Cronbach's Alpha test, EFA, CFA, and SEM, to affirm the reliability of the measurement scale and the appropriateness of the variables in the research model. Based on the research results, we identify the influencing factors that underlie the article's recommendations.